27+[8+(6x2-12:4):9]-36=
mihaelap:
de ce ai puso de doua ori
Răspunsuri la întrebare
Răspuns de
1
27+[8+(12-3):9]-36=27+(8+9:9)-36=27+(8+1)-36= =27+9-36=36-36=0
Răspuns de
0
27 + [ 8+ ( 6 X 2 - 12 : 4 ) : 9 ] - 36 =
= 27 + [ 8 + 9 : 9 ] - 36
= 27 + 9 - 36
= 0
= 27 + [ 8 + 9 : 9 ] - 36
= 27 + 9 - 36
= 0
Alte întrebări interesante
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
10 ani în urmă
Limba română,
10 ani în urmă
Limba română,
10 ani în urmă
Matematică,
10 ani în urmă